Clostridium butyricum, a butyrate-producing potential probiotic, alleviates experimental colitis through epidermal growth factor receptor activation. Issue 13 (9th June 2022) - Wu, Jingyi; Zhou, Bingqian; Pang, Xiaoqi; Song, Xueli; Gu, Yu; Xie, Runxiang; Liu, Tianyu; Xu, Xin; Wang, Bangmao; Cao, Hailong
Abstract : Clostridium butyricum could ameliorate DSS-induced colitis through the transactivation of EGFR signaling induced by EGFR ligands (HB-EGF and AREG) in intestinal epithelial cells. Abstract : Inflammatory bowel disease (IBD) is an idiopathic inflammatory bowel disease. Modulation of gut microbiota with dietary and nutritional targets is a feasible strategy for the prevention and treatment of IBD. In this study, we focused on Clostridium butyricum Prazmowski (CB), a butyrate-producing potential probiotic. We found that CB feeding decreased the disease activity index, colon inflammation/injury score and cell apoptosis in an experimental colitis mouse model, as well as elevated the level of SCFAs in cecal feces. CB could also balance the inflammatory cytokines, protect tight junctions, and increase the number of goblet cells and MUC2 production in mice, accompanied by EGFR signaling activation triggered by heparin-binding epidermal growth factor (HB-EGF) and amphiregulin (AREG). From the perspective of mechanism, the CB supernatant (CBS) stimulated EGFR activation in colon epithelial cell lines in concentration-dependent and time-dependent manners. CBS reduced the damage of tight junctions induced by H2 O2, and inhibition of EGFR could suppress the protective effect of CBS. In conclusion, CB could protect the gut barrier and alleviate experimental colitis through the transactivation of EGFR signaling in intestinal epithelial cells induced by ligands (HB-EGF and AREG). This study identified the potential efficacy of CB as a preventive strategy for IBD and showed the broad prospect of CB as a food supplement.